2016
DOI: 10.1177/1526602815626870
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Complication After Endovascular Aneurysm Repair

Abstract: After publication of a few such cases with the older Zenith device, the union between the suprarenal stent and main body was reinforced in 2002 to prevent this complication. Since modification of the device, this sequela had not been described. The reappearance of this complication underscores the need for continued surveillance, considering that these late events may require a reintervention to maintain the clinical success of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1,[6][7][8] On further review, however, several cases have also been reported in devices inserted after design modification. Torres-Blanco et al ( 2016) reported two cases of suprarenal stent disconnection in Zenith devices inserted in 2006, 9 and Lindstrom et al ( 2016) reported two cases in devices inserted in 2011 and 2012, respectively. 10 Thus, whilst device modification may have strengthened this area of the stent graft, there remains cases of weakness and separation at this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[6][7][8] On further review, however, several cases have also been reported in devices inserted after design modification. Torres-Blanco et al ( 2016) reported two cases of suprarenal stent disconnection in Zenith devices inserted in 2006, 9 and Lindstrom et al ( 2016) reported two cases in devices inserted in 2011 and 2012, respectively. 10 Thus, whilst device modification may have strengthened this area of the stent graft, there remains cases of weakness and separation at this point.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was however noted to have a short aneurysm neck, an anatomical factor identified in previously reported cases of separation. 6,[8][9][10] While the patient's past history of thrombectomy soon after the index procedure is relevant, as instrumentation may have exerted significant tractional forces on the graft and its attachments, normal surveillance imaging multiple years after this intervention indicates that this did not compromise the graft.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, double suturing was implemented by the manufacturer to increase stability between the main body and uncovered segment. 10 , 11 , 12 As EVAR has superseded open aortic repair for aneurysmal disease, device failure has become more commonly reported. A major contributing factor to failed EVAR devices are their use beyond the advised instructions for use, a practice that has been largely supported by the literature to result in higher rates of device failure.…”
Section: Discussionmentioning
confidence: 99%